Synergistic Anti-Biofilm Activity of Stingless Bee Honey and Binahong Leaves Extract Against Staphylococcus aureus - Fieona; Tiara Halidah Ratnasari; Paula Mariana Kustiawan (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
Biofilm formation by Staphylococcus aureus is a major virulence factor contributing to antibiotic resistance. This study investigated the synergistic anti-biofilm activity of stingless bee honey (Homotrigona apicalis) combined with binahong leaves extract (Anredera cordifolia) against S. aureus in vitro. Binahong leaves were macerated using 96% ethanol. Anti-biofilm activity was assessed using a microbroth dilution crystal violet assay in 96-well plates. Five combination ratios (100% Binahong [K1], 100% honey [K2], 75:25 [K3], 50:50 [K4], and 25:75 [K5]) were tested at six concentrations (0.25–8%) and incubated at 37.5°C for 24, 48, and 72 hours. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, and terpenoids. All combinations exhibited concentration-dependent anti-biofilm activity, with the 50:50 combination (K4) showed the most stable and effective inhibition profile across all concentrations and incubation times. The minimum biofilm inhibitory concentrations for 50% and 90% inhibition (MBIC₅₀ and MBIC₉₀) were 0.25% and 8%, respectively. These results demonstrate that stingless bee honey (Homotrigona apicalis) and Binahong leaves extract exhibit strong synergistic anti-biofilm activity, highlighting their potential as alternative agents against S. aureus biofilms. Keywords: Anti-biofilm, Synergistic, Honey, Binahong, Staphylococcus aureus